Das Berliner TransitionsProgramm. Sektorübergreifendes Strukturprogramm zur Transition in die Erwachsenenmedizin - Nolting, Hans-Dieter (De Gruyter, 2016)
The Berlin Transitions Program (BTP) is an interdisciplinary structural program that offers professional case management to help young people with chronic diseases make the transition from pediatric to adult medicine. It is the first program of its kind and serves as a model for a coordinated nationwide transition concept now being reimbursed by a growing number of health insurers.